A review on sensing mechanisms and strategies for telomerase activity detection - Wang, Danni; Xue, Wanyi; Ren, Xiuyan; Xu, Zhangrun (TrAC, Trends in analytical chemistry (Regular ed.), 2021)
Telomerase is a valuable biomarker for early diagnosis and prognosis of cancer, as well as anticancer-drug screening. In this review, we focus on the general sensing mechanisms behind the advanced methods for telomerase activity detection. In terms of the unique properties of telomerase-extended primers, these sensing mechanisms are predominantly classified into three categories: i) mechanism based on hybridization reaction between DNA probes and extended primers, ii) mechanism based on guanine-rich tail of extended primers, iii) mechanism based on electronegativity of extended primers. Advanced telomerase assays corresponding to each sensing mechanism are then critically reviewed. Finally, we discuss current limitations of each sensing strategy and briefly illustrate our perspectives on future research directions in the field of telomerase activity analysis. [Display omitted] •Insights for mechanisms of advanced telomerase assays were provided.•Telomerase assays were classified according to the sensing mechanisms.•Advantages and current limitations of the sensing strategies were elucidated.•Perspectives on the future research directions were briefly illustrated.